Determinants of E. Coli Contamination in Household Drinking Water in Paduresan, Imogiri, Bantul, Indonesia - Sudarwati Sudarwati; Dyah Suryani; Sulistyawati Sulistyawati (Universitas Ibn Khaldun Bogor, 2026)
This study aimed to analyze the determinants of Escherichia coli (E. coli) presence in household drinking water in Paduresan Hamlet, Imogiri, Bantul using a cross-sectional design involving 106 households selected through proportional random sampling. Data were collected using structured questionnaires, observational checklists, and laboratory examination of drinking water samples for E. coli. Bivariate analysis using the Chi-square test showed no significant association between mother’s education level (PR = 1.041; 95% CI: 0.872–1.242; p = 0.879), knowledge (PR = 0.926; 95% CI: 0.764–1.121; p = 0.572), attitudes (PR = 0.992; 95% CI: 0.835–1.179; p = 1.000), raw water protection (PR = 0.988; 95% CI: 0.820–1.191; p = 1.000), and drinking water storage practices (PR = 0.938; 95% CI: 0.784–1.123; p = 0.653) with the presence of E. coli in household drinking water, although a high prevalence of contamination was observed, with 83% of samples testing positive. The findings indicate that socio-demographic and behavioral factors were not significantly associated with E. coli contamination, suggesting that environmental and infrastructural factors may play a more dominant role in determining drinking water quality in the study area.